2006
DOI: 10.1002/jnr.20993
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Myh9 in the mammalian cochlea: Localization within the stereocilia

Abstract: Mutations of non-muscle myosin Type IIA or MYH9 are linked to syndromic or nonsyndromic hearing loss. The biologic function of MYH9 in the auditory organ and the pathophysiology of its dysfunction remain to be determined. The mouse represents an excellent model for investigating the biologic role of MYH9 in the cells and tissues affected by its dysfunction. A primary step toward the understanding of the role of MYH9 in hearing and its dysfunction is the documentation of its cellular and sub-cellular localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Studies in rodents showed that NMMHC-IIA is expressed in the hair cells of the organ of Corti, spiral ligament and spiral limbus, with only minimal expression within the spiral ganglion (Lalwani et al 2000;Mhatre et al 2006). In hair cells, NMMHC-IIA was localized along the length of the stereocilia, the cuticular plate, and the plasma membrane (Mhatre et al 2006;Lalwani et al 2008).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies in rodents showed that NMMHC-IIA is expressed in the hair cells of the organ of Corti, spiral ligament and spiral limbus, with only minimal expression within the spiral ganglion (Lalwani et al 2000;Mhatre et al 2006). In hair cells, NMMHC-IIA was localized along the length of the stereocilia, the cuticular plate, and the plasma membrane (Mhatre et al 2006;Lalwani et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…These cells are supposed to play a role in providing anchorage for surrounding cells or developing or reacting to tension generated in the basilar membrane-spiral ligament complex (Henson et al 1984). Mhatre et al (2006) hypothesized that dysfunction of MYH9 could contribute to SNHL by disrupting the functions mediated by the fibrocytes of the spiral ligament. Indeed, the observation that cochlear implantation has a good outcome in MYH9-RD patients is consistent with these pathogenetic hypotheses, as the cochlear implant directly stimulates the spiral ganglion and thereby bypasses hair cell stereocilia and spiral ligament.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the absence of a phenotype in the other target organs may reflect relatively lower sensitivity of the assays used to uncover the differences. Myh9 within the outer and inner hair cells (Mhatre et al 2004) including their stereocilia (Mhatre et al 2006) suggests that dysfunction and/or haploinsufficiency of Myh9 can lead to lead loss of hair cell integrity and hearing. The diminished OHC function in the outliers supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of other myosin isoforms has been reported in stereocilia and the cuticular plate, in addition to myosin 7a and myosin 1c, to date myosin 15a (see below), myosin 6 [33], and myosin IIa [54] have been identified. Understanding the interactions between these different myosin molecules and their significance in transducer channel adaptation requires further investigation.…”
Section: Myosin 1cmentioning
confidence: 94%